School of Evidence-Based Medicine: The Cerrahpaşa Medical Faculty Practice of Evidence-Based Medicine Training - Çakmakkaya, Özlem Serpil; Demirbaş, Kaan Can; Yaman, Muhittin Onur; Kasapçopur, Özgür; Erginöz, Ethem (Cerrahpaşa Medical Journal, 2021)
Objective: The aim of this study is to introduce and to determine the effectiveness of the School of Evidence-Based Medicine training program, which uses distance learning methods, regarding students’ Evidence-Based Medicine knowledge and skills acquisition and their level of satisfaction with the program. Methods: This study is an experimental investigation using pre-test and post-test evaluations. The knowledge and skill acquisition of the students at the end of the training program was evaluated with the Fresno Test, which was adapted to Turkish with a study conducted at Cerrahpaşa Medical Faculty. In addition, homework and midterm exams were used to evaluate the outcomes. Satisfaction levels were determined by a satisfaction questionnaire consisting of two parts, “Opinions about the Online Training Method” and “Opinions on the Training Program”. Results: The students’ score of the Turkish Fresno Test was 53.3±16.6 (Mean±SD) pre-training and 136.8±19.8 post-training (p<0.001). The overall satisfaction level with the training program was 8.9±1.03 out of 10 points (10 is the highest, 1 is the lowest level of satisfaction). The qualitative and quantitative data obtained from the program evaluation will be used to develop the existing program. Conclusion: The School of Evidence Based Medicine was offered as an elective course in the spring semester of the 2019-2020 academic year. The program, which started in the form of formal education, continued with distance education method due to the Covid-19 Global Outbreak that affected the whole world. The evaluation results indicate that the program was effective in improving students’ knowledge and skills in Evidence-Based Medicine. Students reported a high level of satisfaction with the program. Distance education was viewed unfavorable by students compared to face-to-face education. Cite this article as: Çakmakkaya ÖS, Demirbaş KC, Yaman MO, Kasapçopur Ö, Erginöz E. School of Evidence-Based Medicine: The Cerrahpaşa Medical Faculty Practice of Evidence-Based Medicine Training. Cerrahpaşa Med J 2021; 45(1): 33-42.